Cooperation in symmetric and asymmetric prisoner's dilemma games - Martin Beckenkamp; Heike Hennig-Schmidt; Frank P. Maier-Rigaud (Max Planck Institute for Research on Collective Goods, 2006)
We experimentally study the effect of asymmetry on cooperation in a 40 period prisoner's dilemma game in fixed partner design. We distinguish between a high and low payoff symmetric prisoner's dilemma and an asymmetric game combined out of both symmetric ones. Asymmetry significantly decreases cooperation, as low-type players are more likely to defect after mutual cooperation while high-type players initiate cooperation more often than the former. Asymmetry also has a significant negative effect on the stability of cooperation rendering long sequences of mutual cooperation extremely rare.
Keywords: C81; D70; C91; 330; Symmetry; Asymmetry; Prisoner's Dilemma; Experiments